The Role of the Nurul Mahdor Jam'iyah Sholawat Assembly in Instilling Religious Values in Jati Agung Youth in South Lampung - Yudha Kapindo; Istihana; Zahra Rahmatika (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The purpose of this study was to determine and analyze the role of the Majelis Sholawat Jam'iyah Nurul Mahdor in instilling religious values in adolescents in Jati Agung, South Lampung. In addition, this study also aims to examine the factors that support and hinder the Majelis Sholawat in its efforts to guide adolescents to have an understanding and practice of religious values. This study uses a qualitative approach with data collection methods in the form of observation, in-depth interviews, and documentation studies. Observations were made on various activities carried out by the assembly, while interviews were conducted with adolescents, mentors, and administrators of the assembly. All data collected were then analyzed descriptively-interpretively to understand in depth how the role and influence of the assembly's activities on the development of faith, worship, and morals of adolescents. The results of the study show that the Majelis Sholawat Nurul Mahdor has a very important role in shaping the religious character of adolescents. Through various routine activities such as reciting sholawat, monthly religious studies, and hadrah art training, this assembly instills values of faith, fosters a sense of love for Allah and the Prophet Muhammad, and increases awareness in carrying out daily worship. The presence of the assembly also helps shape teenagers' self-confidence as devout Muslims, as well as guiding them to become individuals with noble character through teaching morals and ethics in Islamic teachings.